An Analysis of the "Bio" / "Eco" Products Market, Referring to the EU and Romania - Ionel Bostan (CES Working Papers, 2016)
The EU and Canada represent the largest market in the world for the sale of ecological products attracting exports from many third countries and recording a total sale of 95% of the worldwide total market. The European market for ecological products – also known as “bio” / “eco” – in absolute figures – is somewhere around 20 billiards euro/year, and in the case of Romania, the market for those products varies around 200 million euro/year. According to European legislation, there are harmonized provisions and procedures for the import of ecological products which can be implemented in two ways: either by complying with the EU legislation on ecologic products, or based on the equivalence between the existent standards and control systems. In many European countries, the operators on such a market obey the rules established by Legislation for ecologic productions strictly. In Romania, a sanctioning system against those economic operators who fraudulently use product labels suggesting they are organic products has just recently been considered. Taking into consideration all these aspects, the present paper relies on the most recent bibliographic and statistical references in this field.
Keywords: K2; Q1; Q5; 330; environment; ecological production; organic food; biological agriculture; exports; internal market; regulations on “bio”/“eco” products